DC Communities: Transformative Building Blocks of the Emerging Energy Infrastructure - Maximiliano Lainfiesta Herrera (MDPI AG, 2021)
Serious environmental concerns call for revolutionary solutions to cope with the harmful effects of the conventional energy landscape. Therefore, residential and commercial customers require cleaner and more reliable energy sources as they become more dependent on energy for daily and critical needs. In this case, transitioning to a cleaner energy economy is of paramount importance for both the environment and the utilities as well as the end-users. The desired transformation will require the deployment of massive amounts of clean energy sources. Many of these resources, such as solar photovoltaic (PV), provide electricity in the form of direct current (DC) that enables the return of DC grids to the electric power arena. The electric system has slowly transitioned to DC, mainly on the demand side. In recent years, modern electronic devices, lighting systems, and an increased number of appliances (≈22% of the residential and commercial loads) have adopted DC systems. Studies suggest that DC loads would account for more than 50% of the available loads in the next few years. Furthermore, the growing proliferation of electric vehicles influx is another example of a successful DC application. From this perspective, the viability of returning to the DC distribution system in the form of DC community grids is explored. We start by defining the DC community grid, which is followed by introducing the benefits of adopting DC at the distribution level. Finally, a summarizing outlook of successful pilot cases, projections of DC community deployment, barriers and concerns, strategies to address barriers and concerns, and suggestions for future research directions are presented. This perspective could shed new light on the building blocks of the transformed energy landscape for various stakeholders.